A comparative study of volume control ventilation versus pressure control ventilation in patients of trauma - Gupta, Achin; Dalvi, Naina P.; Tendolkar, Bharati (International Journal of Research in Medical Sciences, 2016)
Background: Trauma patients may require mechanical ventilation secondary to the respiratory centre depression or acute respiratory distress syndrome (ARDS). It has become increasingly accepted that mechanical ventilation, although often life-saving, can contribute to lung injury. This concept has led to implementation of lung protective ventilation strategies. Methods: This is a prospective, double blind, comparative study in which sixty patients of intubated trauma patients on mechanical ventilation expected at least for five days are included. They were divided in group V where patients were put on volume control ventilation for four days and group-P where patients were put on volume control for two days and pressure control for next two days, after initial stabilization. Each patient was evaluated for ventilation parameters (partial pressure of oxygen, partial pressure of carbon dioxide, peak inspiratory pressure), chest X ray findings and outcome of the patient, keeping the hemodynamic stability and medications same in all patients of both groups. Results: The demographic data like age, weight, and sex were comparable in both volume and pressure control groups.. Baseline ventilation parameters were compared between the groups at every eight hours. During the study we found that there was significant and better oxygenation in pressure control ventilation than volume, less increase in peak inspiratory pressure in pressure controlled ventilation than volume controlled. Other parameters like partial pressure of carbon dioxide also showed less increase in pressure control ventilation. Chest X ray finding showed that the data is comparable and statistically not significant in both the groups. The outcomes of the patients were good in pressure control mode of ventilation than volume control mode and the data was statistically significant. Conclusions: We conclude a better compliance of patients and good respiratory outcome on pressure control than volume. It has better lung compliance with respect to partial pressures of O2 and CO2 and peak inspiratory pressures than the volume control.